Avaliação microestrutural e microquímica de limas reciproc após serem submetidas a diferentes ciclos de uso para preparos em molares inferiores: um estudo ex vivo - Silva, Silvana Jéssica Carlos da (2025)
Proper instrumentation is essential for the disinfection of the root canal system. Nickel-titanium (NiTi) m-Wire reciprocating files, such as Reciproc®, have simplified endodontic preparation due to their flexibility and single-file usage capability. Although single use is recommended by the manufacturer, reuse is a common practice due to sustainability and economic viability concerns, raising questions about the structural and compositional integrity of these instruments. This study aimed to analyze the ultrastructural and compositional changes in Reciproc® R25 files subjected to multiple use cycles in the mesial canals of lower molars, evaluating their reuse potential. Eleven Reciproc® R25 files were used: one unused file and ten files that instrumented one to ten canals, undergoing disinfection and sterilization after each use. The apical 5 mm of the files were qualitatively and structurally evaluated using Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray Spectroscopy (EDS) to identify cracks, cavitations, deformations, and changes in Ni/Ti, Ca/Ni, and Ca/Ti ratios. Data were analyzed using Pearson’s correlation and Student’s t-test (p<0.05). All reused files exhibited debris and a high incidence of deformations (cracks, craters, and barbs), regardless of the number of uses. However, the reduction in Ni/Ti ratios (1–2 mm: 1.1016±0.0308; 3–4 mm: 1.0837±0.0263, p=0.160), Ca/Ni (1–2 mm: 0.0177±0.0283; 3–4 mm: 0.0226±0.0312, p=0.706), and Ca/Ti (1–2 mm: 0.0192±0.0300; 3–4 mm: 0.0239 ±0.0327, p=0.729) was not statistically significant with the number of sterilization cycles or with the presence of deformations. Although Reciproc® files develop visible deformations after a single use, SEM and EDS analyses did not reveal significant changes in the elemental composition of NiTi, suggesting that material loss occurs in a balanced manner. This indicates that while the physical integrity of the files is compromised with reuse, their intrinsic composition remains unaffected.